Strategies for Enhancement of Competitiveness of Small and Medium Industries - Mohideen, Haja; Varadraj, A. (Journal of Engineering Education Transformations, 2007)
The Present-Day knowledge economy demands knowledge-intensive enterprises, which only can survive in the ongoing process of globalization and increased international competition. Knowledge as a factor for competitive advantage has replaced traditional factors like labor and capital.